PERMINTAAN DAN PENAWARAN DALAM EKONOMI MIKRO - Sisilia Venny; Nuraini Asriati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
In micro economics, there is demand and supply, those who demand are consumers and those who supply are producers. If the price goes up, the demand for goods or services goes down, otherwise if the price is low then the demand for goods or services goes up, the statement is the sound of the law of demand in a fixed position (Ceteris Paribus). If the price increases then the supply of goods or services will increase, otherwise if the price decreases then the supply of goods or services will decrease, the statement is the sound of the law of supply in a fixed position (Cateris Paribus). Therefore, it is better if the demand and supply are adjusted according to income, so that the demand for more important goods can be fulfilled properly and the price of the goods or services offer can also adjust the income of consumers, in order to gain profits and aggressively promote the product